Metagenomic next-generation sequencing assisted in the successful treatment of pneumonia caused by Talaromyces marneffei in an immunocompetent patient - Ling-Yan Ye; Xu-Ling Zhao; Jia-Jia Qin; Jian Lin (Journal of Infection in Developing Countries)
Introduction: Talaromyces marneffei (T. marneffei), a kind of endemic opportunistic pathogen, was previously thought to occur in HIV-positive individuals and non-HIV hosts with impaired immune function. However, the infection of T. marneffei in patient with normal immune function was rarely reported.